Exploring students’ EFL writing through the implementation of writing for learning approach (2017)
This document presents the result of a qualitative action research carried out with eleven students of tenth grade at a public school in Bogotá who took part in the research. This action research aimed to exploring students’ EFL writing production through the implementation of writing for learning approach. The data were collected during five sessions developed following the methodology, through teacher's journal, artifacts and interviews.